Effectiveness of surgical decompression in the treatment of a calcifying cystic odontogenic tumor - Yuri Slusarenko da Silva; Adalmir Gonzaga dos Santos Queiroz; Flávio Wellington da Silva Ferraz; Décio dos Santos Pinto Júnior; Fabio Daumas Nunes; Fernando Melhem Elias (University of São Paulo, 2014)
The calcifying odontogenic cystic tumor (CCOT) is a benign lesion of odontogenic origin characterized by an ameloblastoma-like epithelium with ghost cells that may calcify. Despite broadly considered as a cyst, some investigators prefer to classify it as a neoplasm. Clinically, it occurs predominantly during the third decade of life. No difference in gender prevalence has been observed nor predilection of the lesion between maxilla and mandible. The most affected region extends from the incisor tooth to bicuspids. The classic treatment of the lesion is full excision, although a different approach may be determined by the possible association with another odontogenic tumor. Depending on the tumor size and the vicinity with important structures, decompression may be undertaken before its complete removal. The present report describes a case of CCOT with large proportions, located at the right maxilla and extending to the maxillary sinus, nasal cavity, and orbital floor. The treatment option was surgical decompression as the initial procedure, with satisfactory outcome. After partial remission, the lesion was fully removed, and the post-operative follow-up was uneventful.